Recent Advances in Novel Nanostructuring Methods of Perovskite Electrocatalysts for Energy-Related Applications - Xu, Xiaomin; Wang, Wei; Zhou, W.; Shao, Zongping (WILEY-V C H VERLAG GMBH, 2018)
Perovskite oxides hold great promise as efficient electrocatalysts for various energy-related applications owing to their low cost, flexible structure, and high intrinsic catalytic activity. However, conventional synthetic methods can only obtain perovskite catalysts with large particle sizes, small surface areas, and few morphological features, leading to limited catalytic activity and thus posing a major challenge toward real-world applications. Reducing the size of bulk perovskites down to the nanosize represents an efficient way to improve the electrocatalytic performance. A comprehensive overview of recent progress in the nanostructuring of perovskites for catalyzing several key reactions in metal–air batteries, water splitting, and solid oxide fuel cells is provided. A range of synthetic protocols for making perovskite nanostructures are summarized, followed by an emphasis on how each method can be tailored to obtain high-performing perovskite nanocatalysts. These recent advances highlight the enormous potential of nanosized perovskites for facilitating the electrocatalytic reactions. The remaining challenges and future directions are pointed out for the development of next-generation perovskite-based nanostructured catalysts.